Benchmark for three-dimensional explicit asynchronous absorbing layers for ground wave propagation and wave barriers. (March 2021) - Li, Sijia; Brun, Michael; Djeran-Maigre, Irini; Kuznetsov, Sergey
Abstract: This paper presents a benchmark for three-dimensional explicit asynchronous absorbing layers for modeling unbounded domains through a standard displacement-based finite element method: Three-dimensional Perfectly Matched Layers (PML) is compared to recently proposed Absorbing Layers with Increasing Damping (ALID) based on Rayleigh and Kosloff damping formulations. The coupled problem, including the interior subdomain and the absorbing layers, is implemented in the framework of Heterogeneous Asynchronous Time Integrator (HATI), enabling the absorbing layers to be handed with an explicit Central Difference scheme, with fine time steps, independently from the time stepping procedure adopted in the interior subdomain. Simple 3D Lamb's tests are considered by using different kinds of absorbing layers. The superiority of the PML in terms of the accuracy and computation time is highlighted. Finally, realistic 3D applications are investigated, such as the Lamb's test and the study of the screening effect provided by a horizontal wave barrier in mitigating the ground surface vibration generated by an excited plate.